What stole Chinese older adults’ life satisfaction? Integrating medical statistics and machine learning with a life-course perspective using CHARLS data - Zhao, Jing; Wang, Yaya; Du, Xiao Fei; Wang, Shao Peng; Lin, Jun (BioMed Central Ltd, 2026)
Background: As China enters a rapidly aging era, understanding the determinants of life satisfaction among older adults has become a pressing research and policy concern. Life satisfaction in later life is shaped not only by current psychosocial and material conditions but also by accumulated experiences across the life course. Despite increasing attention to healthy aging, few studies have systematically examined how these factors jointly influence life satisfaction. Methods: Using data from 4,627 individuals aged 60 and above drawn from the 2020 wave of the China Health and Retirement Longitudinal Study (CHARLS) merged with the 2014 Life History Survey, this study applied a stage-specific and integrated analytical framework. Generalized Ordered Logit Regression (GOLR) was combined with the XGBoost machine learning algorithm to capture both linear and nonlinear associations, as well as perform individual-level prediction of life satisfaction. This mixed-method approach enabled identification of key determinants across satisfaction levels while allowing for variable interactions and heterogeneity analysis. Results: The results show factors’ heterogeneity across satisfaction levels. At lower levels, present-day psychosocial and material conditions including depressive symptoms, self-rated health, intergenerational relationships, and access to utilities play dominant roles. As satisfaction level increases, early-life factors become increasingly important. Two variables, satisfaction with children relationship and depressive symptoms, consistently influence life satisfaction across all stages. The transition to very satisfaction involves all five domains of predictors, while the highest level of satisfaction is explained by a smaller group of enduring psychological and intergenerational factors. Conclusion: This study provides an integrated and stage-specific understanding of life satisfaction among older Chinese adults. The findings deepen the theoretical understanding of life course influences, social support, and psychological resilience in later life. The study also suggests the need for tailored policy interventions that prioritize mental health care, social engagement, and basic living conditions at lower satisfaction levels, and incorporate early-life experiences and emotional connectedness for those with higher satisfaction.